Storage stability of novel juice blends from watermelon and tamarindo (Research, Society and Development, 2023)
Mixed tropical fruit drinks have been growing on the market due to their sensorial and nutritional characteristics necessary for everyday life. Fruits like watermelon and tamarind are rich in minerals, vitamins and antioxidants. Juices in the form of blends have intensified properties that provide health benefits and a unique flavor. Another advantage with this processing is the reduction of waste, it adds value to the raw material and is promising for the market that has consumers willing to consume foods and drinks that also provide health benefits. In this research, the objective was to develop a mixed fruit juice with stable antioxidant potential during storage. For this, four different formulations were created, F1 (30% tamarind - 20% watermelon), F2 (25% tamarind - 35% watermelon), F3 (20% tamarind - 35% watermelon) F4 (20% tamarind - 65% watermelon). The laboratory experimental methodology of a quantitative nature with physical, chemical and microbiological analyzes at (time 0), after 30 and 90 days of refrigerated storage at a temperature of approximately 10 ºC. The formulations were processed and their stability assessed during storage.